Tanino da acácia negra como inibidor da corrosão de aço API5L X65 em meio ácido - Bettanin, Viviane (2018)
In order to reduce the environmental impacts caused by chemical harmful to the environmental and to human health, the development of natural substances that are able to substitute these dangerous components have been increased. Tannins are a group of natural poliphenolic components extracted from plants that could be used as corrosion inhibitors. This study investigates the utilization of two bark of black wattles (Acacia mearnsii) as corrosion inhibitors, Weibull and Macrospec, in acidic medium and in atmospheric environment and in aqueous CO2 rich medium under high pressure. API 5L X65 steel samples were exposed to a corrosive medium (0.1 M HCl) with different tannin concentrations. The best results were duplicate to an environmental with CO2 saturated water at 15 MPa and 50°C. In order to characterize the specimens scanning electron microscopy by gun field emission, energy dispersive spectroscopy, X ray diffraction, mass loss tests and potenciodynamic polarization tests were used. The results indicated that both tannins, at atmospheric pressure and 0.1 M HCl corrosive environment have similar performance as corrosion inhibitors, and the higher dosage tested (12 g/L) exhibited the best efficiency. However, when the tannins were tested in environment with presence of CO2 under high pressure (15 MPa) and 50ºC the results were different, and only Macrospec tannin had an inhibitory action under the conditions tested.